Magnetic nanoparticle hyperthermia enhancement of cisplatin chemotherapy cancer treatment. (21st October 2013) - Petryk, Alicia A.; Giustini, Andrew J.; Gottesman, Rachel E.; Kaufman, Peter A.; Hoopes, P. Jack
Abstract: Purpose : The purpose of this study was to examine the therapeutic effect of magnetic nanoparticle hyperthermia (mNPH) combined with systemic cisplatin chemotherapy in a murine mammary adenocarcinoma model (MTGB). Materials and methods : An alternating magnetic field (35.8 kA/m at 165 kHz) was used to activate 110 nm hydroxyethyl starch-coated magnetic nanoparticles (mNP) to a thermal dose of 60 min at 43 °C. Intratumoral mNP were delivered at 7.5 mg of Fe/cm 3 of tumour (four equal tumour quadrants). Intraperitoneal cisplatin at 5 mg/kg body weight was administered 1 h prior to mNPH. Tumour regrowth delay time was used to assess the treatment efficacy. Results : mNP hyperthermia, combined with cisplatin, was 1.7 times more effective than mNP hyperthermia alone and 1.4 times more effective than cisplatin alone ( p  < 0.05). Conclusions : Our results demonstrate that mNP hyperthermia can result in a safe and significant therapeutic enhancement for cisplatin cancer therapy.